2018
DOI: 10.1016/j.jiph.2018.07.003
|View full text |Cite
|
Sign up to set email alerts
|

Influenza vaccination situation in Middle-East and North Africa countries: Report of the 7th MENA Influenza Stakeholders Network (MENA-ISN)

Abstract: Participating countries concluded that despite an increase in vaccine uptake observed during the last few years, influenza vaccination coverage remains relatively low. Priority areas should be identified and action plans tailored to each country situation set-up to investigate the best way to move forward.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
17
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 16 publications
(16 reference statements)
5
17
0
Order By: Relevance
“…A 2018 review of influenza surveillance and vaccination in the MENA region reported that out of 518 analyzed samples from cases with influenza like illness 28% had received the influenza vaccine. This is consistent with our findings of 1/3 of children being vaccinated although the report mentions unpublished data of higher vaccination coverage rates reaching 40–60% between 2009–2011 in one large medical center in Beirut area and a rate of 6% across the country inferred from vaccine dose distribution [ 19 ]. These vaccination rates are much lower than what is estimated by the WHO for other childhood immunizations (above 85% for conjugate pneumococcal vaccine and above 90% for DTP, polio, Hib and hepatitis B.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…A 2018 review of influenza surveillance and vaccination in the MENA region reported that out of 518 analyzed samples from cases with influenza like illness 28% had received the influenza vaccine. This is consistent with our findings of 1/3 of children being vaccinated although the report mentions unpublished data of higher vaccination coverage rates reaching 40–60% between 2009–2011 in one large medical center in Beirut area and a rate of 6% across the country inferred from vaccine dose distribution [ 19 ]. These vaccination rates are much lower than what is estimated by the WHO for other childhood immunizations (above 85% for conjugate pneumococcal vaccine and above 90% for DTP, polio, Hib and hepatitis B.…”
Section: Discussionsupporting
confidence: 93%
“…In this review awareness and previous encounters with influenza were the motivators for vaccination whereas fear of side effects, impression of ineffectiveness and lack of strong provider recommendation represented the major barriers to influenza vaccination in Lebanon [ 19 ]. This is consistent with our findings that reveal physician recommendation as the single most important factor in awareness and practice among Lebanese parents.…”
Section: Discussionmentioning
confidence: 99%
“…To gather more data on the availability of influenza vaccines and antiviral drugs in Africa as well as related national policies and guidelines, a survey was conducted by the CDC. However, the coauthors failed to find responding experts in Algeria …”
Section: Discussionmentioning
confidence: 99%
“…Reasons for low vaccine coverage have been reported to include lack of influenza awareness, political and cost issues, and limited collaboration between private and governmental hospitals. 5,6 The importance for HCWs vaccination is not only to prevent them from becoming ill but also to avoid the spread of infection to the patients and the community. Vaccine coverage among HCWs is low, at approximately 30%, and declining in some European countries whereas, in the United States, vaccine coverage has been reported to be approximately 78%.…”
Section: Introductionmentioning
confidence: 99%